Superparamagnetic imposed diatom frustules for the effective removal of phosphates - Toster, J.; Kusumawardani, I.; Eroglu, Ela; Iyer, K.; Rosei, F.; Raston, C. (2014)
Diatom frustules coated with magnetite nanoparticles 21 nm in size were synthesised without the requirement of stabilisers, or prior functionalisation of the frustule surface, with the resulting material exhibiting superparamagnetic behaviour, and with a high capacity for phosphate ion adsorption. © 2014 The Royal Society of Chemistry.